2021
DOI: 10.3389/fpos.2021.633688
|View full text |Cite
|
Sign up to set email alerts
|

Different Pasts for Different Political Folk: Political Orientation Predicts Collective Nostalgia Content

Abstract: Collective nostalgia is a bittersweet emotion that reflects sentimental longing for valued aspects of the past of one’s group. Given that conservatism is typically associated with a general desire to preserve the societal status quo or return society to its traditional way of being, nostalgia has been theorized to be characteristic of those on the political right (i.e., conservatives). In the current work, we proposed and tested the hypothesis that collective nostalgia is experienced by both conservatives and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…Nevertheless, other research demonstrates that feelings of nostalgia, when used strategically, can increase agreement across party lines on divisive political issues such as gun control, inequality, and climatechange (Baldwin & Lammers, 2016;Lammers & Baldwin, 2018). Understanding the role of nostalgia for the self and society, and whether it will harm or help social progress, requires moving toward a more comprehensive approach to the phenomenon (see Stefaniak, Wohl, Sedikides, Smeekes, & Wildschut, 2021 for work along these lines).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other research demonstrates that feelings of nostalgia, when used strategically, can increase agreement across party lines on divisive political issues such as gun control, inequality, and climatechange (Baldwin & Lammers, 2016;Lammers & Baldwin, 2018). Understanding the role of nostalgia for the self and society, and whether it will harm or help social progress, requires moving toward a more comprehensive approach to the phenomenon (see Stefaniak, Wohl, Sedikides, Smeekes, & Wildschut, 2021 for work along these lines).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on what specifically one feels group-based nostalgia for, this affects political orientation differently. To illustrate, while radical right support following nostalgia for society's homogeneity (Stefaniak et al, 2021) or grandiosity (Marchlewska et al, 2018) is intuitive, it seems less straightforward as a consequence of nostalgia for society's preindustrial environment.…”
Section: Group-based and Personal Nostalgia As Two Forms Of Copingmentioning
confidence: 99%
“…Nostalgia is a universal emotion, which expresses the emotional needs of individuals who want to go back to the past [ 16 ]. In the past, nostalgia was often considered negative, as it was characterized by a sense of loss and depression.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Wohl et al [ 24 ] test the impact of collective nostalgia on the relationship of groups, and the results show that the collective nostalgia of group members effectively predicted the prejudice of external groups and anti-immigrant sentiment. Stefaniak et al [ 16 ] explore the collective nostalgia of political figures in the United States, Canada and Britain, and found that conservatives experience more collective nostalgia centered on homogeneity, which is mostly manifested in positive inter-group attitudes, while liberals experience more collective nostalgia centered on openness, which is mostly manifested in negative inter-group attitudes.…”
Section: Theoretical Foundationsmentioning
confidence: 99%